Foreign body ingestion in children: At a glance - Diego Falchi; Toni Risteski (My University, 2022)
This article discusses the symptoms, diagnosis, and treatment options available for children who have accidentally swallowed foreign objects. It may be helpful for primary care physicians to recognize the wide spectrum of presentations of ingested foreign bodies in children. As a result, primary care physicians should emphasize the importance of considering ingested foreign bodies in the differential diagnosis of many respiratory and vague gastrointestinal complaints. In addition to this, it suggests a method for dealing with asymptomatic children who have swallowed a foreign body and identifies certain categories of foreign bodies that call for additional consideration.
Keywords: Children; coin ingestion; endoscopy; foreign body ingestion